(untitled) (Acta Scientiarum. Health Sciences, 2021)
Descriptive, quasi experimental study with pre and post-test, which aimed to investigate the effects of Water Pilates (PA) on urinary incontinence, genital self-image and sexual function of elderly women. The sample consisted of seventeen elderly women aged 60 years or over, from a city in the interior of Rio Grande do Sul. The International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) was used as instruments to assess the impact of UI in quality of life and qualify urinary loss, the Female Sexual Function Index (FSFI) to assess sexual function and Female Genital Self-Image Scale (FGSIS) to assess women’s perception of their own genitalia. The PA protocol was performed twice a week for 50 minutes performed for eight weeks, totaling 16 sessions. The protocol was divided into warm-up, strengthening exercises and stretching. It was observed that the sample was composed of young elderly women (69.5 ± 5.9 years), overweight and with low FSFI and FGSIS scores. There was no significant change in the mean values before and after the intervention of the ICIQ-SF, FGSIS and FSFI scores. It was concluded that the PA method had no effect on urinary loss, sexual function and genital self-image.